Security control of networked systems with deception attacks and packet dropouts: A discrete-time approach. Issue 16 (October 2021) - Hu, Zhipei; Deng, Feiqi; Su, Yongkang; Zhang, Jin; Hu, Songlin
Abstract: This paper is concerned with the security control problem for a class of networked systems subject to deception attacks and packet dropouts. First, by taking into account the deception attacks and packet dropouts in an unified framework, a discrete-time stochastic system is presented. In virtue of matrix exponential computation, an equivalent discrete-time stochastic model is established. Based on this, the security analysis is given by the law of total expectation and some sufficient conditions are provided. Subsequently, a controller is designed. Finally, the effectiveness of the proposed method is illustrated by two examples including a practical power grid system.